PENGARUH PROFITABILITAS, LEVERAGE, LIKUIDITAS, UKURAN PERUSAHAAN DAN KEBIJAKAN DIVIDEN TERHADAP NILAI PERUSAHAAN - Riana R Dewi; Suhendro; Regia Rolanta (Fakultas Ekonomi Dan Bisnis Universitas Bhayangkara Jakarta Raya, 2020)
This study aimed to analyze the effect of profitability, leverage, liquidity, company size and dividend policy on firm value in the Consumer Goods Industry Sector Companies listed on the Stock Exchange in 2015-2018. In this study the Company Values measured using the Price to Book Value (PBV). This research method using descriptive analysis. The technique used is purposive sampling technique, so found 14 Consumer Goods Industry Sector Companies listed on the Stock Exchange from 2015 to 2018 period. The analysis used is multiple linear regression analysis. The results of this study showed that the variables of profitability, liquidity, and dividend policy affects the value of the company, while the company size and leverage variables do not affect the value of the company.